2022
DOI: 10.1111/aphw.12367
|View full text |Cite
|
Sign up to set email alerts
|

The effects of loving‐kindness and compassion meditation on life satisfaction: A systematic review and meta‐analysis

Abstract: Loving‐kindness and compassion meditation (LKCM) was a promising intervention for improving life satisfaction, but previous findings have been inconsistent. The current study provides a systematic review and meta‐analysis, including 23 empirical studies on LKCM with life satisfaction as an outcome variable. The primary meta‐analysis indicated that LKCM significantly enhanced life satisfaction in pre‐post design (g = 0.312, k = 15, n = 451), but the significance disappeared in the additional meta‐analysis based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 39 publications
1
16
1
1
Order By: Relevance
“…First, we reviewed the available literature to identify interventions designed to treat long-lasting BPD symptoms. This review showed that PP exercises and compassion strategies seem to be useful for enhancing well-being [ 17 , 26 , 33 , 47 , ​ 57 ]. Consequently, we developed an intervention based on PP and contemplative practices (for more details see the Wellbeing Training Based on Contemplative Practices [WTCP]) manual: [ 13 , 15 , 26 ]).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we reviewed the available literature to identify interventions designed to treat long-lasting BPD symptoms. This review showed that PP exercises and compassion strategies seem to be useful for enhancing well-being [ 17 , 26 , 33 , 47 , ​ 57 ]. Consequently, we developed an intervention based on PP and contemplative practices (for more details see the Wellbeing Training Based on Contemplative Practices [WTCP]) manual: [ 13 , 15 , 26 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Some mindfulness practices, such as loving-kindness (LK) and self-compassion (SC), are part of a set of DBT skills named “other perspectives on mindfulness” [ 50 ]. LK and SC, along with mindfulness, have proven useful to alleviate suffering and promote well-being ([ 26 , 33 ]; ​ ​[ 53 , 57 ]). Nevertheless, most DBT skills training programs [ 10 , 25 , 50 ] focus on the “core mindfulness skills”, which teach participants how to practice mindfulness.…”
Section: Introductionmentioning
confidence: 99%
“…There was a study demonstrated that mindfulness meditation has positive affect on attention control, emotion regulation and selfawareness through neurocognitive mechanism [7]. Mindfulness and meditation also involved with the change in cognition, memory, social relationship, improve emotional control abilities, and decrease loneliness resulted in various health improvement [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Such practices are similar to imagined intergroup contact in that different types of people are typically brought to mind. However, imagined intergroup contact involves imagining positive interactions with outgroup members while loving-kindness and compassion-based practices typically involve directly cultivating a sense of kindness and friendliness toward whoever has been brought to mind [12,13]. The evidence to date suggests that these types of practices can reduce political intergroup bias [14] (see also [15]), with effects mediated by perceived commonality with the political outgroup [16].…”
Section: Introductionmentioning
confidence: 99%